Afforestation and agroforestry enhance soil nutrient status and carbon sequestration capacity in eastern China. (8th November 2019) - Guo, Jing; Wang, Bo; Wang, Guibin; Wu, Yaqiong; Cao, Fuliang
Abstract: Afforestation and agroforestry both sequester atmospheric carbon (C) and store C in the soil. However, the response of soil nutrients and soil organic carbon (SOC) to these practices has not been fully examined, especially in deep soil layers. We therefore investigated the effects of afforestation and agroforestry on the nutrient contents and organic carbon (OC) stocks within a 100‐cm depth in eastern China. The soil nutrient contents and stoichiometry as well as the SOC contents and stocks exhibited different vertical patterns and varied among the five planting systems. The total nitrogen (TN), total phosphorus (TP), and SOC contents decreased dramatically at a 20‐cm depth, and the total potassium (TK) content exhibited a different pattern. Compared with adjacent croplands and nurseries, the forest plantation and agroforestry systems had higher SOC stocks, ranging from 42.9 to 111.6 t·hm −2 in the whole soil profile. The SOC distribution among the depth gradient varied among planting systems, and the topsoil SOC stocks played crucial roles in total SOC storage within a depth of 100 cm in the cropland and nursery systems. The soil pH and bulk density (BD) were negatively correlated with the SOC content, and a significant positive linear relationship occurred between the TN and SOC contents and between the TP and SOC contents. We recommend that combinations of nitrogen (N) and phosphorus (P) fertilizers would benefit SOC storage and improve stabilization in agroforestry and plantation systems.